EFEK LARVASIDA EKSTRAK ETANOL DAUN BINTANGUR (Chalophyllum inophyllum L.) TERHADAP MORTALITAS LARVA NYAMUK AIR KOTOR (Culex sp.) - Nurpermatasari, Adhisty; Faisal, Ahmad Purnawarman; Nasution, Pratiwi Rukmana (Jurnal Riset Kefarmasian Indonesia, 2023)
The Bintangur plant is a plant that can often be found around the house, its existence as a plant makes its properties less known to the public, all parts of this plant are known to be very useful for various pharmacological effects. Various efforts to prevent diseases transmitted by Culex sp. one of them uses larvicides, so an alternative larvicide from natural ingredients is needed, namely Bintangur. The purpose of this study was to determine the activity of the ethanol extract of Bintangur leaves in killing Culex sp larvae with the control being the larvae that were not given the ethanol extract of Bintangur leaves. The type of research on the activity test of the Bintangur leaf ethanol extract used an experimental research type with a true experiment design with a posttest only control group design. The results showed that the ethanol extract of Bintangur leaves (Chalophyllum Inophyllum L.) was active in killing Culex sp. larvae. with the results of the Reed and Muench test with an LC50 value of 281.84 ppm